Turkey's Accession to the European Union : the politics of exclusion - Hughes, Edel (Routledge research in EU law., 2011)
Turkey's accession to the European Union is undoubtedly one of the Union's most contested potential enlargements. The narrative that dominates the debate surrounding this issue primarily relates to problems such as a lack of respect for fundamental human rights in Turkey, the Kurdish question and the continuing stalemate concerning northern Cyprus. This book looks at these issues, but also proposes that a review of Turkey's experience with the EU in its numerous incarnations suggests that these concerns may mask a deeper disquiet. Whilst there are several questions that Turkey must address, pa.